Sistem Pemantau Kelembapan Tanah Akurat dengan Protokol Zigbee IEEE 802.15.4 pada Platform M2M OpenMTC - Putu Agus Fredy; Maman Abdurohman (Department of Computer Engineering, Engineering Faculty, Universitas Diponegoro, 2018)
This paper presents a study on an accurate soil moisture monitoring system based on its humidity from 9 sensor nodes using wireless sensor network (WSN) and M2M platform. The system used IEEE 802.15.4 (Zigbee) protocol. The system was connected to the application via the OpenMTC M2M platform. This monitoring system can measure soil moisture accurately and provide soil water content status on the application. The system was effective in measuring soil moisture at a distance of 0-25 meters where there was a barrier between gateway and sensor, and at a distance of 0-50 meter in line of sight. The position of the sensors that are within 3 meters of each other and the depth of each sensor 3 cm can measure soil moisture properly.